2015
DOI: 10.1007/s10876-015-0880-z
|View full text |Cite
|
Sign up to set email alerts
|

New Member of Organic Ligand Functionalized TMSP: Synthesis, Characterized and Properties of Na15[(MnII(COOH))3(AsW9O33)2]·15H2O

Abstract: Reaction of [Mn 12 (CH 3 COO) 16 (H 2 O) 4 O 12 ]Á2CH 3 COOHÁ4H 2 O and Na 9 [AsW 9 O 33 ]Á19.5H 2 O in aqueous solution leads to the isolation of a new carboxy group decorated TMSP, Na 15 [(Mn II (COOH)) 3 (AsW 9 O 33 ) 2 ]Á15H 2 O (1). The structure of 1 was characterized by elemental analysis, thermometric analysis and single crystal X-ray diffraction (Crystal data for 1: Trigonal, P-3, a = 12.8804(4) Å , b = 12.8804(4) Å , c = 30.3501(19) Å , V = 4360.6(3) Å 3 , Z = 2). Structural analysis reveals that 1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Coordination of outer acetate ligands has been recorded in [(Mn(COOH))3(α-AsW9O33)2] 15− (Figure 8.c). [62] Magnetic susceptibility studies for these polyanions showed J = 0.07 cm -1 indicating a weak anti-ferromagnetic coupling between the Mn II centres. [62]…”
Section: Other Types Of Terminating Ligandsmentioning
confidence: 91%
See 1 more Smart Citation
“…Coordination of outer acetate ligands has been recorded in [(Mn(COOH))3(α-AsW9O33)2] 15− (Figure 8.c). [62] Magnetic susceptibility studies for these polyanions showed J = 0.07 cm -1 indicating a weak anti-ferromagnetic coupling between the Mn II centres. [62]…”
Section: Other Types Of Terminating Ligandsmentioning
confidence: 91%
“…[62] Magnetic susceptibility studies for these polyanions showed J = 0.07 cm -1 indicating a weak anti-ferromagnetic coupling between the Mn II centres. [62]…”
Section: Other Types Of Terminating Ligandsmentioning
confidence: 91%
“…In case anti-isomerism is switched with syn-orientation, then distortion between the centers may occur. 8c) [86]. Magnetic susceptibility studies for these polyanions showed J = −0.07 cm −1 indicating a weak anti-ferromagnetic coupling between the Mn II centers [86].…”
Section: Hervé Polyanions Sandwiching Two and Four Heterometalsmentioning
confidence: 93%
“…8c) [86]. Magnetic susceptibility studies for these polyanions showed J = −0.07 cm −1 indicating a weak anti-ferromagnetic coupling between the Mn II centers [86].…”
Section: Hervé Polyanions Sandwiching Two and Four Heterometalsmentioning
confidence: 93%